Removal of manganese(II) ions from aqueous solutions by adsorption on activated carbon derived a new precursor: Ziziphus spina-christi seeds - Abdessalem Omri; Mourad Benzina (Alexandria Engineering Journal, 2012)
In this paper, activated carbon was prepared from Ziziphus spina-christi seeds (ZSAC) to remove Mn(II) from aqueous solutions. To characterize the adsorptive characteristics of the produced active carbon, surface area was calculated using the standard Brunauer–Emmet–Teller method. The microstructures of the resultant activated carbon were observed by with scanning electron micrographs. Chemical characterization of the surface resultant activated carbon was studied by Fourier Transform Infrared Spectroscopy. The effects of pH, initial metal ion concentration and temperature on the adsorption performance of ZSAC for Mn(II) ions were examined by batch method. The adsorption equilibrium data were analyzed by Langmuir, Freundlich and Temkin isotherm models. We concluded that maximum adsorption capacity of manganese calculated from Langmuir isotherm was around 172 mg/g.